Design, analysis and fabricate of the humidifier and air freshener / Muhammad Syazwan Fathullah Mohd Yunus and Nor Liawati Abu Othman - Mohd Yunus, Muhammad Syazwan Fathullah; Abu Othman, Nor Liawati (School of Mechanical Engineering, 2022)
Humidifiers are commonly used to humidify a single room such as an office, living room, and else. The common problem that happens in our daily life is the unpleasant smell in our room. To counter this problem, we need something that can eliminate odour. Because of that, we need to develop a humidifier and air freshener by using Arduino. This product can make our air room fresh and also it can humidify the entire room. The humidifier is an effective and simple way to combat exposure to harsh, dry air. Adding a cool mist of water to the air in your room with a mini humidifier while you sleep could help to alleviate these uncomfortable symptoms, often overnight. There are two objectives in this project which are to design a humidifier and air freshener by using the Solidwork software and to fabricate the humidifier and air freshener for use in the room space. This humidifier and air freshener provide 2 functions which are humidifying the room air and to freshen up the room space. The advantages of this product can help people to moisturise the skin to prevent dry skin and prevent unpleasant room odours. More importantly, this product is easy to use and easy to maintain